2009
DOI: 10.1016/j.crvi.2009.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Esca et Black Dead Arm : deux acteurs majeurs des maladies du bois chez la Vigne

Abstract: Les maladies du bois de la vigne sont très dommageables pour la pérennité du patrimoine viticole car les parasites responsables de ces maladies attaquent les organes pérennes provoquant à plus ou moins long terme la mort du cep. L'esca et le BDA sont des acteurs majeurs de ces maladies de dépérissement. Les symptômes s'expriment au niveau du bois par la formation de nécroses sectorielles et/ou centrales, par la présence de bandes brunes ou de chancres et au niveau foliaire par des décolorations et des dessèche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 78 publications
0
58
0
Order By: Relevance
“…A presumed saprotrophy for the esca fungi is also in line with observations that esca development is generally patchy in a vineyard and does not spread from a particular point of infection (Mugnai et al 1999;Surico et al 2006). Disease incidence and identity of presumed trunk diseaseassociated fungi have been shown to vary in function of studied grapevine cultivars, geography, soil type and climate (Armengol et al 2001;Bertsch et al 2009;Casieri et al 2009;Edwards et al 2001;Larignon 2012;Larignon and Dubos 1997;Marchi 2001;Mugnai et al 1999;Surico et al 2006). At the same time, the host specificity of escaassociated fungal species is very broad and nearly all identified fungi that were recovered in this study have also been reported from other hosts (Online Resource 2).…”
Section: Discussionmentioning
confidence: 99%
“…A presumed saprotrophy for the esca fungi is also in line with observations that esca development is generally patchy in a vineyard and does not spread from a particular point of infection (Mugnai et al 1999;Surico et al 2006). Disease incidence and identity of presumed trunk diseaseassociated fungi have been shown to vary in function of studied grapevine cultivars, geography, soil type and climate (Armengol et al 2001;Bertsch et al 2009;Casieri et al 2009;Edwards et al 2001;Larignon 2012;Larignon and Dubos 1997;Marchi 2001;Mugnai et al 1999;Surico et al 2006). At the same time, the host specificity of escaassociated fungal species is very broad and nearly all identified fungi that were recovered in this study have also been reported from other hosts (Online Resource 2).…”
Section: Discussionmentioning
confidence: 99%
“…Symptom expression caused by Botryosphaeriaceae species has been shown to differ from region to region and among different grapevine cultivars (110,209). Typical disease symptoms include cankers and other dieback symptoms such as bud mortality, leaf chlorosis, fruit rot, sectorial wood necrosis, shoot dieback, cane bleaching, and graft union failure ( Fig.…”
Section: Importance and Impact Of Fungal Trunk Pathogens In Young Vinmentioning
confidence: 99%
“…For example, Chardonnay infected by trunk disease-causing agents presents less symptomatic leaves compared with other cultivars. To date, no resistant cultivar has been reported (Surico et al 2006;Larignon et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…A cross in the wood shows a yellow to orange area at the edge of a brown band, limited to a few millimetres in depth, where the vessels are clogged. In woody tissue, grey sectorial necrosis can be observed, and this is equivalent to black dots on a cross (Larignon 2012). Given that pathogens can be found in the wood but never in the leaves of infected plants, it was hypothesised that the observed leaf and berry symptoms are actually caused by extracellular compounds produced by fungi in the discoloured woody tissues of the trunk, which then translocate to the leaves via the transpiration stream (Mugnai et al 1999).…”
Section: Introductionmentioning
confidence: 99%